2020
DOI: 10.7554/elife.51737
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mRNA translation by a photoriboswitch

Abstract: Optogenetic tools have revolutionized the study of receptor-mediated processes, but such tools are lacking for RNA-controlled systems. In particular, light-activated regulatory RNAs are needed for spatiotemporal control of gene expression. To fill this gap, we used in vitro selection to isolate a novel riboswitch that selectively binds the trans isoform of a stiff-stilbene (amino-tSS)–a rapidly and reversibly photoisomerizing small molecule. Structural probing revealed that the RNA binds amino-tSS about 100-ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…125 However, recently, a few stiff stilbene derivatives were equipped with solubilizing groups and characterized in DMSO-water mixtures, buffer solutions and even in vivo. 116,[141][142][143] The compounds were reversibly switchable over several cycles, 141 however, photo-induced oxidation was observed in some cases (cf. Fig.…”
Section: Photoswitches Relying On the Isomerization About Double-bondsmentioning
confidence: 99%
“…125 However, recently, a few stiff stilbene derivatives were equipped with solubilizing groups and characterized in DMSO-water mixtures, buffer solutions and even in vivo. 116,[141][142][143] The compounds were reversibly switchable over several cycles, 141 however, photo-induced oxidation was observed in some cases (cf. Fig.…”
Section: Photoswitches Relying On the Isomerization About Double-bondsmentioning
confidence: 99%
“…The peculiarities of the aptamer-ligand interactions allowed to obtain systems with highly efficient, light-controllable switching of the ligand binding state (''ON/OFF binding''). Thus, four examples of photoswitchable binders for RNA aptamers were reported that are based on the reversible photoinduced transformations of spiropyran 4, 42 benzodihydropyrene 5, 43 azobenzene 6, 44 and stiff-stilbene 7 45 (Schemes 2c, 3 and Table 1). The RNA aptamers that bind specifically only to one of the two forms of the ligands 4-6 were selected in vitro from RNA aptamer libraries by the Systematic Evolution of Ligands by EXperimental enrichment (SELEX) procedure 46 i.e.…”
Section: View Article Onlinementioning
confidence: 99%
“…In the case of stiffstilbene 7, the selection was performed using an RNA pool derived from a bacterial SAM-1 riboswitch by replacing its ligand-binding domain with a random region of 45 nucleotides and partially randomizing the terminator and anti-terminator hairpins. 45 As a result, the selected RNA aptamer was isolated as a fused construct together with a riboswitch expression platform. The reversible photoswitching between the isomers of ligands 4-7 gave the systems an advantage of accomplishing repeated binding/dissociation cycles with RNA.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…[71] In another recent study,Míšek and Luptak described that the photocontrol of binding of as tiff-stilbene amino alcohol to m-RNAc an be used to regulate protein expression. [72]…”
Section: Toward Biological Applicationmentioning
confidence: 99%